Prognosis impact of multiple novel lymphocyte‐based inflammatory indices in patients with initially diagnosed coronary artery disease - Yi Gao; Geng Bai; Yuqing Li; Bo Yu; Ziqiang Guo; Xiaolin Chen; Tong Liu; Guangping Li (Immunity, Inflammation and Disease)
Abstract Background This study aimed to evaluate six novel lymphocyte‐based inflammatory markers (neutrophil‐lymphocyte ratio, monocyte‐lymphocyte ratio, platelet‐lymphocyte ratio [PLR], systemic immune inflammation index [SII], systemic inflammatory response index, and systemic immune inflammation response index [SIIRI]) in patients with newly diagnosed coronary artery disease [CAD]. Methods A total of 959 patients newly diagnosed with CAD and underwent diagnostic coronary angiography were enrolled in this study and followed for major adverse cardiovascular events (MACEs), including cardiovascular death, nonfatal myocardial infarction, and nonfatal stroke. The best cutoff value was used to compare the six indicators. Cox risk regression analysis evaluated the relationship between novel lymphocyte‐based inflammatory markers and MACEs in newly diagnosed CAD patients. Results During a mean follow‐up period of 33.3 ± 9.9 months, 229 (23.9%) MACEs were identified. Multivariate Cox regression analysis showed that only SIIRI (hazard ratio [HR]: 5.853; 95% confidence interval [CI]: 4.092–8.371; p < .001) and PLR (HR: 1.725; 95% CI: 1.214–2.452; p = .002) were independent predictors of MACEs. Nevertheless, following the adjustment for covariates, only the SIIRI was found to be a significant predictor MACEs and its corresponding specific endpoint occurrences. The predictive ability of the model was improved when six different inflammatory markers were added to the basic model established by traditional risk factors, namely, the C‐index increased, and the SIIRI increased most significantly (AUC: 0.778; 95% CI: 0.743–0.812; p < .001). However, among the six novel inflammatory markers, only SIIRI had improved net reclassification improvement (NRI) and integrated discrimination improvement (IDI) (NRI: 0.187; 95% CI: 0.115–0.259, p < .001. IDI: 0.135; 95% CI: 0.111–0.159, p < .001), which was superior to the basic model established by traditional risk factors. Conclusions SIIRI is independent predictor of MACEs in newly diagnosed CAD patients. SIIRI was superior to other measures in predicting MACEs. The combination of SIIRI and traditional risk factors can more accurately predict MACEs.